Functional Analysis of PTH1R Variants Found in Primary Failure of Eruption. (April 2020) - Izumida, E.; Suzawa, T.; Miyamoto, Y.; Yamada, A.; Otsu, M.; Saito, T.; Yamaguchi, T.; Nishimura, K.; Ohtaka, M.; Nakanishi, M.; Yoshimura, K.; Sasa, K.; et al.
Although many variants of the parathyroid hormone 1 receptor (PTH1R) gene are known to be associated with primary failure of eruption (PFE), the mechanisms underlying the link remains poorly understood. We here performed functional analyses of PTH1R variants reported in PFE patients—namely, 356C>T (P119L), 395C>T (P132L), 439C>T (R147C), and 1148G>A (R383Q)—using HeLa cells with a lentiviral vector-mediated genetic modification. Two particular variants, P119L and P132L, had severe reduction in a level of N -linked glycosylation when compared with wild-type PTH1R, whereas the other 2 showed modest alteration. PTH1R having P119L or P132L showed marked decrease in the affinity to PTH1-34, which likely led to severely impaired cAMP accumulation upon stimulation in cells expressing these mutants, highlighting the importance of these 2 amino acid residues for ligand-mediated proper functioning of PTH1R. To further gain insights into PTH1R functions, we established the induced pluripotent stem cell (iPSC) lines from a patient with PFE and the heterozygous P132L mutation. When differentiated into osteoblastic-lineage cells, PFE-iPSCs showed no abnormality in mineralization. The mRNA expression of RUNX2, SP7, and BGLAP, the osteoblastic differentiation-related genes, and that of PTH1R were augmented in both PFE-iPSC-derived cells and control iPSC-derived cells in the presence of bone morphogenetic protein 2. Also, active vitamin D3 induced the expression of RANKL, a major key factor for osteoclastogenesis, equally in osteoblastic cells derived from control and PFE-iPSCs. In sharp contrast, exposure to PTH1-34 resulted in no induction of RANKL mRNA expression in the cells expressing P132L variant PTH1R, consistent with the idea that a type of heterozygous PTH1R gene mutation would spoil PTH-dependent response in osteoblasts. Collectively, this study demonstrates a link between PFE-associated genetic alteration and causative functional impairment of PTH1R, as well as a utility of iPSC-based disease modeling for future elucidation of pathogenesis in genetic disorders, including PFE.